Therapeutic response of cysteamine in the treatment of melasma (Research, Society and Development, 2020)
The aim of this study was to evaluate how the use of cysteamine in the treatment of melasma has been studied in the literature. This is a qualitative research of the type integrative review to identify productions on topics associated with topical treatment of melasma with cysteamine. The search for the articles was carried out through the Scopus, Science Direct and Pubmed databases using the terms: “melasma” and “cysteamine” and corresponding terms in Portuguese. The research followed the inclusion criteria: a) articles b) be available in full text c) time frame from 01/01/2010 to 31/03/2020 d) studies available in Portuguese, English or Spanish. As exclusion criteria, texts that were unrelated to the theme or had duplicates were disregarded. Of the amount of 11 articles presented, 6 were selected by affinity to the search theme, with 5 articles excluded by the aforementioned criteria. The therapeutic response of cysteamine for the treatment of melasma is positive, reducing hyperpigmented lesions and with controllable adverse effects over the duration of treatment. There was no evidence of the use of cysteamine associated with other active substances or dermatological procedures.